2015
DOI: 10.1016/j.mimet.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metagenomic DNA extraction procedures on the identifiable endophytic bacterial diversity in Sorghum bicolor (L. Moench)

Abstract: Keywords:Metagenomic DNA extraction Endophytic bacteria Sorghum root and stem t-RFLP Pyrosequencing Culture-independent studies rely on the quantity and quality of the extracted environmental metagenomic DNA (mDNA). To fully access the plant tissue microbiome, the extracted plant mDNA should allow optimal PCR applications and the genetic content must be representative of the total microbial diversity. In this study, we evaluated the endophytic bacterial diversity retrieved using different mDNA extraction proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 136 publications
6
37
0
Order By: Relevance
“…The genera Massilia, Pseudomonas , and Limnohabitans were predominant in the three grass species. This is only partly in line with a previous study showing that Pseudomonas, Rhizobium , and Bacillus were the most abundant genera in roots and shoots of sorghum21. Similar results were obtained by Robinson et al 7.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The genera Massilia, Pseudomonas , and Limnohabitans were predominant in the three grass species. This is only partly in line with a previous study showing that Pseudomonas, Rhizobium , and Bacillus were the most abundant genera in roots and shoots of sorghum21. Similar results were obtained by Robinson et al 7.…”
Section: Discussionsupporting
confidence: 92%
“…In total, 71 samples of the grass species L. perenne, D. glomerata , and F. rubra in two consecutive years were analyzed. Consistent with previous work72021, bacterial endophyte communities were dominated by five phyla. The genera Massilia, Pseudomonas , and Limnohabitans were predominant in the three grass species.…”
Section: Discussionsupporting
confidence: 91%
“…Extraction requirements and recommendations A range of methods are used to extract DNA from plant tissues, including fungal and bacterial endophytes Maropola et al 2015). Recent extractions of arbuscular mycorrhizal fungal (AMF) DNA from plant roots have used the DNeasy PowerSoil ® kit Padamsee et al 2016), or the DNeasy Plant kit for AMF in the roots of Ammophila arenaria (Johansen et al 2015).…”
Section: Extraction Of Dna From Plant Tissuementioning
confidence: 99%
“…It is possible that the DNeasy PowerSoil ® kit gives superior results in samples of tree roots that are higher in phenolic compounds in comparison to softer tissue like grass roots. DNeasy PowerSoil ® or PowerMax ® kits are routinely used for sample material, including plant tissues, that are high in inhibitory compounds (Dineen et al 2010;Maropola et al 2015), even though relatively low DNA yields are reported for some sample material (Maropola et al 2015). While there is little evidence upon which to base favouring one extraction method over others, standardisation on one method shown to be adequate (or at least not inadequate) will improve the comparability of results obtained from different laboratories.…”
Section: Extraction Of Dna From Plant Tissuementioning
confidence: 99%
“…Tsurumaru et al (2015) analyzed a metagenome of the bacterial community associated with the taproot of sugar beet (Beta vulgari L.) The study found that Alphaproteobacteria are dominant, followed by the Actinobacteria and the Betaproteobacteria. Another metagenomic study of the sorghum root and stem microbiome revealed that the two tissues harboured significantly different composition of bacterial communities, but both were dominated by agriculturally important genera such as Microbacterium, Agrobacterium, Sphingobacterium, Herbaspirillum, Erwinia, Pseudomonas and Stenotrophomonas (Maropola et al, 2015).…”
Section: Occurrence and Diversity Of Bacterial Endophytes In Agricultmentioning
confidence: 99%